Thief who stole my heart the material life of sacred bronzes from Chola India, 855-1280 - Dehejia, Vidya (Princeton Princeton University Press, 2021)
"From the ninth through the thirteenth centuries, the Chola dynasty of southern India produced bronze sacred statues of Hindu deities, each one unique, whose beautiful representations of the body were viewed as expressions of holiness and religious purity. Yet these sculptures of Shiva, also known as the "Thief Who Stole My Heart," were not kept enclosed in temples. During festivals, they were adorned with jewels and flowers and paraded through towns as a part of Chola citizens' social and ritual life. The history of the Chola society remains little-examined by contemporary scholars, and these statues have never been studied within their rich historical and social contexts. In this book, based on her 2016 Mellon Lectures, author Vidya Dehejia examines the sacred bronzes as material objects that participated in the festivals and lives of Chola citizens, using them as ways to shed light on little-known Chola religious traditions, daily activities, and socioeconomic practices. For instance, Dehejia hypothesizes that the state of Tamil Nadu, where these bronzes were found, must have traded with Sri Lanka in order to supply the two hundred tons of copper required for the statues, and that this may have influenced the Chola dynasty's broader political engagement with the island. She also uses the bronzes to address the Chola dynasty's wealth, the empire's position along the trade route between Aden and China, the role of women patrons, and the thousands of public records that were inscribed on temple walls. By tracing how these bronzes combined ideas of the sacred with the sensuousness and joy of town festivals, Dehejia highlights the Chola dynasty's remarkable understanding of deities as active participants in human society"--